Ethanol dehydration activity on hydrothermally stable LaPxOy catalysts synthesized using CTAB template - Goh, Yi Ling Eileen (2013)
Nanocrystalline LaPxOy with various starting P to La ratios from 0.5 to 2.0 catalysts were prepared by a sol–gel method using cetyl trimethylammonium bromide (CTAB) as template. The catalysts were thoroughly characterized by N2 physisorption, powder X-ray diffraction (XRD), temperature programmed desorption (TPD) of NH3, solid state 31P and 1H nuclear magnetic resonance (NMR), and transmission electron microscopy (TEM) techniques. XRD results indicate the presence of predominantly monazite LaPO4 with minor amounts of (≤3.0 wt%) rhabdophane LaPO4 phase in the samples with starting P/La ratios of 1.0 and 1.5. NH3-TPD results show an increasing trend in the total acidity with increase in P/La ratio. These catalysts were tested in the selective ethanol dehydration in the temperature range between 250 and 400 °C. The catalyst activity (μmol/h/m2) is increased with P/La ratio and the catalyst with highest P/La ratio of 2.0 exhibiting the highest ethanol dehydration activity. The ethanol conversion increased with reaction temperature, reaching 100% at 350 °C and remains unchanged at higher temperatures. On the other hand, the ethylene selectivity is also increased up to 350 °C and then decreased with further increase of reaction temperature. At a P/La ratio of 2, the CTAB templated LaPxOy catalyst showed higher catalytic activities compared to the LaPxOy by hydrothermal method without any template.